2002
DOI: 10.1007/s00417-002-0427-5
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 inhibitor transiently delays inherited retinal degeneration in C3H mice carrying the rd gene

Abstract: The caspase-3 inhibitor was transiently effective in delaying retinal degeneration through inhibition of the apoptosis of photoreceptor cells in rd gene-carrying mice. The use of caspase-3 inhibitors may have therapeutic applications in the treatment of human retinal degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 23 publications
3
38
0
Order By: Relevance
“…Akt signaling strongly inhibits caspase cleavage cascades (Kermer et al, 2000;Barber et al, 2001;Vincent and Feldman, 2002). Activated caspase-3 correlates with photoreceptor degeneration in various rodent models (Liu et al, 1999;Yoshizawa et al, 2002). Activated caspase-3 accumulates in the Irs2 Ϫ/Ϫ retina, which may explain the observed increase in photoreceptor cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Akt signaling strongly inhibits caspase cleavage cascades (Kermer et al, 2000;Barber et al, 2001;Vincent and Feldman, 2002). Activated caspase-3 correlates with photoreceptor degeneration in various rodent models (Liu et al, 1999;Yoshizawa et al, 2002). Activated caspase-3 accumulates in the Irs2 Ϫ/Ϫ retina, which may explain the observed increase in photoreceptor cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some studies have demonstrated caspase activation in rd1 retinae from the 2nd to 3rd postnatal week, i.e. at peak or postpeak of photoreceptor cell apoptosis (15)(16)(17), Doonan et al (18) were unable to detect increased caspase expression or activation at these and earlier time points in the same tissue, and caspase inhibition or ablation of caspase-3 failed to rescue rd1 photoreceptors from apoptosis (19,20). It has also been shown that rd1 photoreceptors degenerate irrespective of the expression of p53, a tumor suppressor gene involved in several types of apoptosis (21), or c-Fos (22), which by contrast is entirely essential for light-induced photoreceptor degeneration (23).…”
mentioning
confidence: 93%
“…Although apoptosis often involves caspases, these play only a minor role, if any, in the rd1 degeneration. For instance, relevant caspase activation is absent during the degeneration (Kim et al, 2002;Doonan et al, 2003) and interventions of the caspase cascade fail to preserve the rd1 photoreceptors (Yoshizawa et al, 2002;Zeiss et al, 2004).…”
Section: Introductionmentioning
confidence: 99%